Antigenic Cross-Reactivity Between SARS-CoV-2 S1-RBD and Its Receptor ACE2 - Lai, Yen-Chung; Cheng, Yu-Wei; Chao, Chiao-Hsuan; Chang, Yu-Ying; Chen, Chi-De; Tsai, Wei-Jiun; Wang, Shuying; Lin, Yee-Shin; Chang, Chih-Peng; Chuang, Woei-Jer; Chen, Li-Yin; Wang, Ying-Ren; et al. (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emerging virus responsible for the ongoing COVID-19 pandemic. SARS-CoV-2 binds to the human cell receptor angiotensin-converting enzyme 2 (ACE2) through its receptor-binding domain in the S1 subunit of the spike protein (S1-RBD). The serum levels of autoantibodies against ACE2 are significantly higher in patients with COVID-19 than in controls and are associated with disease severity. However, the mechanisms through which these anti-ACE2 antibodies are induced during SARS-CoV-2 infection are unclear. In this study, we confirmed the increase in antibodies against ACE2 in patients with COVID-19 and found a positive correlation between the amounts of antibodies against ACE2 and S1-RBD. Moreover, antibody binding to ACE2 was significantly decreased in some patients with COVID-19 after preadsorption of the sera with S1-RBD, which indicated that antibodies against S1-RBD can cross-react with ACE2. To confirm this possibility, mice were immunized with recombinant S1-RBD to generate monoclonal antibodies (mAbs). Two mAbs (127 and 150) that could bind to both S1-RBD and ACE2 were isolated. However, the binding affinities of these mAbs to ACE2 vs. S1-RBD were relatively low as determined by Biacore analysis. Epitope mapping using synthetic overlapping peptides and hydrogen deuterium exchange mass spectrometry (HDX-MS) revealed that the amino acid residues P463, F464, E465, R466, D467 and E471 of S1-RBD were critical for the recognition by mAbs 127 and 150. On the other hand, Western blotting analysis showed that these mAbs could recognize ACE2 only in native but not denatured form, indicating the ACE2 epitopes recognized by these mAbs were conformation-dependent. Due to the binding affinity of mAb 127 to ACE2 was much higher than mAb 150, the footprint of mAb 127 on ACE2 was further analyzed by negative-stain transmission electron microscopy imaging and predicted by antigen-antibody docking. Together, our results suggest that ACE2-cross-reactive anti-S1-RBD antibodies can be induced during SARS-CoV-2 infection due to potential antigenic cross-reactivity between S1-RBD and its receptor ACE2.